2020
DOI: 10.1093/mnras/staa093
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of rest-frame UV properties, Ly α EWs, and the SFR–stellar mass relation at z ∼ 2–6 for SC4K LAEs

Abstract: We explore deep rest-frame UV to FIR data in the COSMOS field to measure the individual spectral energy distributions (SED) of the ∼ 4000 SC4K (Sobral et al. 2018a) Lyman-α (Lyα) emitters (LAEs) at z ∼ 2 − 6. We find typical stellar masses of 10 9.3±0.6 M and star formation rates (SFR) of SFR SED = 4.5 +8.8 −2.5 M yr −1 and SFR Lyα = 5.9 +6.3 −2.6 M yr −1 , combined with very blue UV slopes of β = −2.0 +0.3 −0.5 , but with significant variations within the population. M UV and β are correlated in a similar way… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 130 publications
(253 reference statements)
14
86
1
Order By: Relevance
“…In fact, studying the SFR-M star main sequence derived from the best-fitting SSP models (Fig. 15) we find that both pure LAEs and LAE-LBGs are placed above the mean main sequence, as also found in Santos et al (2020), indicating that they are indeed experimenting a recent star-forming episode.…”
Section: Sfr-m Star Relation and Stellar Mass Growth Implicationssupporting
confidence: 58%
See 1 more Smart Citation
“…In fact, studying the SFR-M star main sequence derived from the best-fitting SSP models (Fig. 15) we find that both pure LAEs and LAE-LBGs are placed above the mean main sequence, as also found in Santos et al (2020), indicating that they are indeed experimenting a recent star-forming episode.…”
Section: Sfr-m Star Relation and Stellar Mass Growth Implicationssupporting
confidence: 58%
“…Moreover, the SFRs derived through the Lyα line luminosity can be strongly affected by resonant scattering. For a recent detailed study of the SFR-M star relation estimating SFRs of high-z LAEs through their Lyα luminosity, see, e.g., Santos et al (2020). The so-called SFR-M star main sequence (Fig.…”
Section: Sfr-m Star Relationmentioning
confidence: 99%
“…The intrinsic shape of the Lyα EW distribution is known to be UV-magnitude dependent, and in general UV-bright galaxies have low EWs in Lyα (e.g., Ando et al 2006; Stark et al 2010;Schaerer et al 2011;Cassata et al 2015;Furusawa et al 2016;Wold et al 2017;Hashimoto et al 2017;Jung et al 2018). Additionally, Santos et al (2020) present no significant redshift evolution of the Lyα EW at W 0 = 129 +11 −11 using the full sample of SC4K (Sobral et al 2018) LAEs at z ∼ 2 -6, but find a strong W 0 dependency on M UV and stellar mass. Thus, we need to be careful to interpret the redshift dependence of the EW distribution, as sample selection of spectroscopic observations would place a bias on the derived W 0 .…”
Section: The W 0 Dependence On M Uvmentioning
confidence: 71%
“…Importantly, recent studies have been reported a sign of different evolution of the Lyα EW in bright and faint objects into the epoch of reionization (e.g., Zheng et al 2017;Mason et al 2018b) whereas a decreasing W 0 with increasing UV continuum brightness is seen at lower redshift (e.g., Ando et al 2006;Stark et al 2010;Schaerer et al 2011;Cassata et al 2015;Furusawa et al 2016;Wold et al 2017;Hashimoto et al 2017;Oyarzún et al 2017;Santos et al 2020). Our measurements in Table 2 also show an apparent upturn of W 0 at the brightest magnitude bin, which is consistent with the other studies at this redshift.…”
Section: The W 0 Dependence On M Uvmentioning
confidence: 99%
“…An increasing number of recent works has been focusing on the study of high-redshift Lyman-α emitters (LAEs), objects showing prominent rest-frame Lyα emission within a spectrum (usually) devoided of other line features (e.g., Cassata et al 2011;Nakajima et al 2018). The spectral properties of LAEs are usually interpreted as to be coming from young ( 50 Myr) and low-mass (M * < 10 10 M ) galaxies (e.g., Wilkins et al 2011;Amorín et al 2017;Hao et al 2018;Santos et al 2020) with small rest-frame UV half-light radii ( R 1 − 2 Kpc, as in e.g., Møller & Warren 1998;Lai et al 2008;Bond et al 2012;Guaita et al 2015;Kobayashi et al 2016;Ribeiro et al 2016;Bouwens et al 2017a;Paulino-Afonso et al 2018) which are actively star-forming (SFR ∼ 1 − 100 M /yr) and dust-poor (dust attenuation A V < 0.2, see e.g., Gawiser et al 2006Gawiser et al , 2007Guaita et al 2011;Nilsson et al 2011;Bouwens et al 2017b;Arrabal Haro et al 2020). When observed at high redshift, isolated and grouped LAEs would represent the progenitors of present-day galaxies and clusters, respectively, hence providing extremely valuable insights about structure formation (e.g., Matsuda et al 2004Matsuda et al , 2005Venemans et al 2005;Gawiser et al 2007;Overzier et al 2008;Guaita et al 2010;Mei et al 2015;Bouwens et al 2017b; Khostovan et al 2019).…”
Section: Introductionmentioning
confidence: 99%